Applying slicing in an extended visual C++ environment - Chen, Cuimin. (2008)
In recent years, a large amount of software has been developed. The need for maintaining and improving software systems has risen dramatically. How to reuse software becomes a very important problem. However, by using the existing technologies, it is difficult to identify the section of codes that implement functionality to help programmers in maintaining or reusing existing systems. To address this problem, Tan [22] proposed a novel representation, Data Flow Net, which can directly trace the functionalities to implementation artifacts.